Estimating the implied cost of carbon in future scenarios using a CGE model: The Case of Colorado. (March 2017) - Hannum, Christopher; Cutler, Harvey; Iverson, Terrence; Keyser, David
Abstract: Using Colorado as a case study, we develop a state-level computable general equilibrium (CGE) model that reflects the roles of coal, natural gas, wind, solar, and hydroelectricity in supplying electricity. We focus on the economic impact of implementing Colorado's existing Renewable Portfolio Standard, updated in 2013. This requires that 25% of state generation come from qualifying renewable sources by 2020. We evaluate the policy under a variety of assumptions regarding wind integration costs and assumptions on the persistence of federal subsidies for wind. Specifically, we estimate the implied price of carbon as the carbon price at which a state-level policy would pass a state-level cost-benefit analysis, taking account of estimated greenhouse gas emission reductions and ancillary benefits from corresponding reductions in criteria pollutants. Our findings suggest that without the Production Tax Credit (federal aid), the state policy of mandating renewable power generation (RPS) is costly to state actors, with an implied cost of carbon of about 17 per ton of CO2 with a 3% discount rate. Federal aid makes the decision between natural gas and wind nearly cost neutral for Colorado. Highlights: If variability cost is low and renewables are federally subsidized, RPS is beneficial. With no PTC or high variability cost, drop in real consumption less than 0.1%. With PTC phaseout and high variability cost ICP is low, between 7.16 and 11.45. With no PTC and high variability cost ICP is between 12.66 and 17.34 per ton.